Perspectives on pictographs| Differences in rock art recording frameworks of the Rattlesnake Canyon pictograph panel - Lindsay, Audrey K. (Northern Arizona University, 2015)
Rock art documentation often draws from a range of recording perspectives, in which each framework facilitates different recording goals, preconceptions, and methods. As a result, each recording project collects different types of information from a rock art panel. The intricate and visually striking rock art murals painted on rockshelter walls in the Lower Pecos Canyonlands of southwestern Texas demand and benefit from the application of artistic, avocational archaeological, and professional archaeological documentation frameworks. This research provided a case study that analyzed different recording projects of the Rattlesnake Canyon mural (41VV180), a Pecos River style pictograph panel located in the Lower Pecos Canyonlands. I applied a critical theoretical framework and the concept of “capta” to review and analyze the rock art documentation perspectives, methods, and materials collected from three major recording projects of the Rattlesnake Canyon mural. I focused on projects completed by artist Forrest Kirkland, the Texas Archeological Society (TAS) avocational archaeological Rock Art Task Force (RATF), and an illustration of the Shumla Archaeological Research and Education Center’s (Shumla) recording process, to examine differences between artistic, avocational archaeological, and professional archaeological recording frameworks and methods. This case study demonstrated the ways in which the specific framework or perspective of a recorder influenced the methods selected for documentation and the types of information collected during rock art recording. The results of this critical analysis showed that the different recording projects shared a similar goal: to preserve the Rattlesnake Canyon mural for future generations and continued archaeological study. The three different projects, however, drew from distinct recording frameworks that influenced the overall conception of the panel, the methods selected for recording, and the types of information collected. In this case study, I suggested that rock art researchers, specifically those from a professional archaeological framework, value the incorporation of different perspectives and methods into rock art documentation. The inclusion of varied perspectives and methods brings different skillsets and expertise to rock art recording. In addition, each recording project gathers different kinds of information from rock art murals that can be used in different ways by subsequent recorders, researchers, and land managers. This critical analysis of previous rock art recording projects also demonstrated that existing rock art documentation legacy materials continue to serve as productive resources for further research, management, and public education purposes.